Transition from intravenous or subcutaneous prostacyclin therapy to inhaled treprostinil in patients with pulmonary arterial hypertension: a retrospective case series. (8th May 2014) - Enderby, C. Y.; Soukup, M.; Al Omari, M.; Zeiger, T.; Burger, C.
Summary What is known and objective Inhaled treprostinil represents an attractive alternative to the other available prostacyclin formulations by obviating the use of continuous infusions and its associated risks. Published evidence describing the process of transition from infusion prostacyclin therapy to inhaled treprostinil is limited. The purpose of this report is to describe an inpatient protocol for transitioning patients with pulmonary arterial hypertension (PAH) from intravenous (IV) or subcutaneous (SQ) prostacyclin therapy to inhaled treprostinil. Methods A retrospective case cohort study was performed evaluating medical records of three patients undergoing transition from IV/SQ continuous infusion prostacyclin therapy to inhaled treprostinil. The transition protocol and clinical data were collected prospectively. Results and discussion Haemodynamics, six‐min walk distance (6MWD), World Health Organization (WHO) functional class, modified Borg Dyspnea Score and brain natriuretic peptide prior to and after transition remained similar. All patients were receiving concomitant oral PAH medications prior to and after conversion. Adverse effects during the change were mild. No patients discontinued inhaled treprostinil following transition. At long‐term follow‐up, functional class remained stable at WHO functional class II or better. Patient 1 and Patient 3 demonstrated stable to modest improvement in 6MWD, whereas Patient 2 had a slight decrease in 6MWD. The transition to inhaled treprostinil from IV/SQ infusion prostacyclin therapy appears to be safe in carefully selected patients. What is new and conclusion Our report describes a standard method used to transition patients from IV/SQ infusion prostacyclin to inhaled treprostinil.